IL‐21 regulates macrophage activation in human monocytic THP‐1‐derived macrophages. Issue 1 (11th August 2021) - Jian, Leilei; Li, Changhong; Sun, Lin; Ma, Zhenzhen; Wang, Xinyu; Yu, Ruohan; Liu, Xiangyuan; Zhao, Jinxia
Abstract: Background: Interleukin‐21 (IL‐21) has a regulatory effect on various immune cells. Its effect on macrophage function remains unclear. Aims: This study aimed to investigate the effect of IL‐21 on the macrophages‐mediated inflammatory response and explore its mechanism. Materials & Methods: Phorbol myristate acetate was used to induce THP‐1‐derived macrophages. Then, cells were stimulated with IL‐21 and/or lipopolysaccharide (LPS). To determine the effect of IL‐21 on the production of inflammatory factors in THP‐1‐derived macrophages, the messenger RNA (mRNA) and protein levels of IL‐6, tumor necrosis factor‐α (TNF‐α), IL‐8, and IL‐10 were detected by real‐time polymerase chain reaction (RT‐PCR) and enzyme‐linked immunosorbent assay (ELISA), respectively. Meanwhile, to explore the effect of IL‐21 on macrophage polarization, macrophage phenotype, gene expression, and cytokine secretion mediated by THP‐1‐derived macrophage were detected by flow cytometry, RT‐PCR, and ELISA. Results: First, we found that the IL‐21 receptor was expressed in THP‐1‐derived macrophages. IL‐21 enhanced LPS‐mediated TNF‐α, IL‐6, and IL‐10 production in THP‐1‐derived macrophages. During the polarization of THP‐1‐derived macrophages to M1‐like macrophages, IL‐21 induced the expression of macrophage surface markers CD86 and CD80, and related genes, such as TNF‐α, IL‐6, IL‐1β, and DC‐SIGN mRNA, inhibited Dectin‐1 mRNA expression and promoted the secretion of TNF‐α. During the polarization of THP‐1‐derived macrophages to M2‐like macrophages, IL‐21 enhanced the expression of macrophage surface markers CD86 and CD163, and related genes, such as TNF‐α, IL‐1β, IL‐10, Dectin‐1, and DC‐SIGN mRNA, and promoted the secretion of IL‐10. Conclusion: IL‐21 promotes LPS‐mediated production of inflammatory cytokines by THP‐1‐derived macrophages; IL‐21 plays a two‐way regulatory role in THP‐1‐derived macrophage polarization. Highlights: IL‐21R is expressed in human monocytic THP‐1 derived macrophages. IL‐21 up‐regulates the gene expression and protein secretion of TNF‐α, IL‐6, and IL‐10 in LPS‐mediated THP‐1 derived macrophages. IL‐21 plays a two‐way regulatory role in THP‐1 derived macrophage polarization. Abstract : IL‐21 regulates macrophage activation in human monocytic THP‐1 cells derived macrophages.